On the relevance of chaos for halo stars in the solar neighbourhood - Maffione, Nicolás Pablo (2015)
Fil: Maffione, Nicolas P. Universidad Nacional de la Plata. Facultad de Ciencias Astronómicas y Geofísicas; Argentina